2022
DOI: 10.24323/akademik-gida.1097814
|View full text |Cite
|
Sign up to set email alerts
|

Şalgam Suyunun Depolanması Sırasındaki Kalite Özellikleri Üzerine Üretim Yöntemi ve Sıcaklığının Etkisi

Abstract: Shalgam has been a fermented beverage produced in high amounts and consumed widely in Turkey in recent years. Despite its potential, there is no specific processing method or temperature for the production of shalgam beverages. Therefore, in this study, some changes in shalgam obtained by using two production processes (conventional and rapid processes) at 25 and 35°C were monitored during 4 months of storage. In particular, changes in color values that might affect product quality and attractiveness were infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…The L* value of the control sample was 11.8 while that of the PEF-treated sample was 13.2. The obtained L* values are consistent with the results of Tangüler et al 38 who found the lightness values of shalgam juices between 13.56 and 14.46.…”
Section: Total Dry Matter Content and Color Attributessupporting
confidence: 92%
See 4 more Smart Citations
“…The L* value of the control sample was 11.8 while that of the PEF-treated sample was 13.2. The obtained L* values are consistent with the results of Tangüler et al 38 who found the lightness values of shalgam juices between 13.56 and 14.46.…”
Section: Total Dry Matter Content and Color Attributessupporting
confidence: 92%
“…Depending on the activities of LAB, Arslan et al 46 reported that the titratable acidity of shalgam juice increased during cold storage. The titratable acidity determined by Tangüler et al 38 in shalgam juice samples at the end of the 4 months storage period is lower (3.54-4.85 g L −1 ) than those of this study. This may be due to the use of different amounts of black carrots in production.…”
Section: The Ph and Post-acidification During Cold Storagecontrasting
confidence: 85%
See 3 more Smart Citations